Metastatic involvement of the central nervous system in gynecological cancer - Yu. S. Sidorenko; S. V. Grigorov; V. E. Plotnikova (Опухоли женской репродуктивной системы)
Metastatic involvement of the central nervous system (CNS) is very rarely observed in gynecological cancer . Ten case histories were analyzed in patients with malignancies of the cervix uteri, endometrium, and ovaries concurrent with metastatic involvement of the brain and spine. The CNS involvement was metachronous in all the patients. The mean interval between the detection of a primary tumor and the emergence of metastases was 3.1, 4.5, and 2.3 years for cervix uteri, corpus uteri, and ovarian cancers, respectively. All patients with gynecological cancer are indicated to undergo a follow-up including neurological examination and X-ray or magnetic resonance imaging of the brain and spine. When meat static CNS involvement is detected, multimodality treatment involving surgery followed by chemoradiation therapy is recommended.